Explaining Secondary Students’ Career Intentions for Technology and Engineering Jobs Using an Expectancy-Value Model - Smit, Robbert; Robin, Nicolas; De Toffol, Christina (Frontiers in Education, 2020)
This research presents an empirical model based on expectancy-value theory to explain students’ attitudes towards science-based technology. The question is how students’ attitudes are connected with their aspirations for a career in the technology and engineering fields. There is a high demand for technology professionals, but students’ interest in such careers is low. The context of this study is a cooperation project involving local industry and Swiss secondary schools that aims to foster students’ interest in science-based technology. We conducted a mix-methods study with a sample of 337 students in secondary school (grades 7-9) and 12 science teachers. Based on the questionnaire data, we created a structural equation model to analyse the relationships between students’ expectancy-value attitudes and career interests. Context variables, such as gender, parents’ professions, and having a workshop at home complement the model. With the help of the data collected in the teacher interviews, the results were validated and elaborated. The findings indicate students’ attitudes and interest in science-based technology were rather low in general, and as expected, they were significantly lower for girls. Our 2-factor empirical model showed a stronger focus on application than on theory. Self-concept and values were predictors of career interests, but not of interest in applied science. Context variables also played a significant role. Triangulation of the data helped validate the measured constructs. In conclusion, our results indicate that school science lessons might not offer sufficient experiences in applied science to secondary school students. Interest in a career in the technology and engineering fields can be triggered by integrating more engineering experiences in the science classroom.